The Precuneus Contributes to Embodied Scene Construction for Singing in an Opera - Tanaka, Shoji; Kirino, Eiji (Frontiers in Human Neuroscience, 2021)
Performing an opera requires singers on stage to process mental imagery and theory of mind tasks in conjunction with singing and action control. Although it is conceivable that the precuneus, as a posterior hub of the default mode network, plays an important role in opera performance, how the precuneus contributes to opera performance has not been elucidated yet. In this study, we aimed to investigate the contribution of the precuneus to singing in an opera. Since the precuneus processes mental scenes, which are multimodal and integrative, we hypothesized that it is involved in opera performance by integrating multimodal information required for performing a character in an opera. We tested this hypothesis by analyzing the functional connectivity of the precuneus during imagined singing and rest. This study included 42 opera singers who underwent functional magnetic resonance imaging when performing “imagined operatic singing” with their eyes closed. During imagined singing, the precuneus showed increased functional connectivity with brain regions related to language, mirror neuron, socio-cognitive/emotional, and reward processing. Our findings suggest that, with the aid of its widespread connectivity, the precuneus and its network allow embodiment and multimodal integration of mental scenes. This information processing is necessary for imagined singing as well as performing an opera. We propose a novel role of the precuneus in opera performance.